In-situ dissolution rates of silicate minerals and associated bacterial communities in the critical zone (Strengbach catchment, France). (15th March 2019) - Wild, Bastien; Daval, Damien; Beaulieu, Emilie; Pierret, Marie-Claire; Viville, Daniel; Imfeld, Gwenaël
Abstract: The weathering of silicate minerals in the Critical Zone (CZ) is fundamental for numerous environmental and societal issues. Despite decades of efforts to accurately record biogeochemical variables controlling mineral reactivity in the field and to reproduce them in the laboratory, weathering rate estimates still differ from those observed in natural settings. Here we examine the biogeochemical environment of mineral surfaces exposed to contrasted weathering conditions in various compartments of a temperate CZ (Strengbach observatory, France). A novel approach was developed to probe both in-situ mineral dissolution rates and bacterial diversity associated with mineral surfaces. Labradorite and olivine minerals were either buried in the A and C horizons of a soil profile, directly exposed to meteoric fluids or immersed in stream water. Dissolution rates recorded in the soil profile were up to 2 orders of magnitude slower than those predicted using a numerical weathering model. Samples directly exposed to meteoric fluids exhibited contrasted dissolution rates that could not be explained by simple abiotic weathering, while dissolution rates of samples incubated in stream water were particularly low. In soil profiles, the field-laboratory discrepancy by up to 2 orders of magnitude was attributed to heterogeneity of fluid circulation and local variation of reaction conditions. Mineral substrates changed bacterial communities of the mineralosphere after 9 and 20 months of incubation in the CZ. However, we observed that this effect could be delayed or driven by extrinsic factors. Although mineral probes in soil horizons were enriched in bacterial phylotypes potentially involved in mineral weathering (e.g., Pseudomonas sp., Collimonas sp., Burkholderia sp., Janthinobacterium sp., Leifsonia sp., and Arthrobacter sp.), the relative contribution of biotic weathering could not be quantified in-situ . Altogether, the heterogeneity of in-situ mineral dissolution rates in compartments of the CZ underscores the need to improve spatial characterization of hydrogeochemical properties at the soil profile scale, and to evaluate quantitatively the role of microbial communities in mineral weathering.